Risk Assessment Due to Population Exposure to Lead Particles Emitted from Domestic Electrical Generators - Nabeel Hashim Ameen; Mohannad Kh. Mohammad; Takrid M. Nafae (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Portable and stationary electrical generators became quite popular in Iraq soon after the shortage in national electrical energy after 2003. Multi step risk assessment process is used in this study in the assessment of risks caused by contamination of indoor air by lead particles emitted from domestic electrical generators. Two portable electrical generators are tested under controlled indoor conditions (Radial LG (0.9 keV) fueled with benzene and oil and TigMax (3 keV), fueled with benzene only). Lead particles in air were sampled by using portable dust sampler (Sniffer, L-30). The atmospheric particulate sampling process is carried out in a flat located in the first floor of a three stories building located in Baghdad city, Al-Zafarania region. The lead concentration in the digested filter papers is measured by using atomic absorption spectrophotometer (Buck, USA). Dose-to-risk conversion factor is applied in this study to estimate the potential cancer risk to Baghdad’s population related to continuous inhalation of airborne lead at the mean observed concentrations. The results of toxicity analysis indicate that public exposure to airborne lead at the mean observed concentration of 4.991  g/m3 can increase the risk of cancer at a rate of 12 extra cancer cases in a group of million exposed individuals. Males are found to be at greater risk than females because of higher inhalation rates. Children are found to be the most sensitive group due to low body weight (about 101 expected additional cancer cases in a group of million exposed child).